Expert System Diagnosa Anak Penderita Autism Dengan Metode Forward Chaining Menggunakan Bahasa Pemograman Java Dan Database Mysql - Ramadini, Yane; Mardison; Aggy Pramana Gusman (Riset Sinergi Indonesia (RISINDO), 2025)
Autism disorders in a person generally suffer from birth, lack of sensitivity and parental knowledge about it is the problem so that the disorder is not detected quickly. For some people who are unfamiliar with this, it is very difficult to find information about places that provide this service. Because the process is too long, or lack of socialization for parents who do not understand this disorder. The problems that exist in the UPTD for Disability Services and Inclusive Education which are still diagnosing by relying on experts. The author makes an expert system that can diagnose children with autism with the forward chaining method, namely by answering questions related to the symptoms of autistic disorders according to the symptoms felt. It is hoped that the UPTD for Disability Services and Inclusive Education can be helped, and with this system, the service will be faster and also help the performance of employees at the UPTD for Disability Services and Inclusive Education.